Abstinence-based treatment of comorbid eating disorders and ultra-processed food addiction - Thompson, Susan Peirce; Jacobs, M. Joy; Wiss, David A. (Frontiers in Psychiatry, 2025)
While not officially recognized as a clinical diagnosis, ultra-processed food addiction (UPFA) is an increasingly observed phenomenon that frequently co-occurs with eating disorders (EDs). Yet, treatment remains both understudied and controversial. Many challenges exist when treating patients with comorbid UPFA/ED, particularly in the context of the polarizing debate between abstinence-based and moderation-based approaches to nutrition intervention. We present three vignettes illustrating diverse trajectories of recovery when an abstinence-based approach is explored by a patient presenting with ED symptoms. Ultimately, some patients will recover with abstinence, while others may be harmed and fare better with a moderation-based approach. This dichotomy appears difficult for many patients and clinicians to navigate, particularly since integrative middle-ground approaches remain less characterized. Patients deserve individualized treatment plans from open-minded, experienced clinicians who can comprehensively assess genetic vulnerability; upbringing; and current neurobiological, psychological, and social/cultural presentation. We argue for a nuanced, multidisciplinary approach that may combine elements of both abstinence and moderation, tailored to the patient’s specific needs, emphasizing the importance of cross-disciplinary collaboration. More research is needed to develop evidence-based, patient-centered treatment options for UPFA in the context of other food- and body-related pathology.